The social media overture of the pan-European Stop-ACTA protest: An empirical examination of participatory coordination in connective action - Mercea, Dan; Funk, Andreas (Convergence (London, England), 2016)
As the latest instalments of protest from the Arab Spring to Occupy and beyond are digested in scholarly work, they point to a scalable, informal structure that develops as an impermanent framework for performing coordinational tasks formerly associated with collective organizations. Whilst a substitution of this nature appears a distinct possibility with social media, the participatory dynamics at the heart of such connective action remain largely uncharted. This article scrutinizes the scope for the participatory development of motivations and resources to undertake collective action. For this purpose, it reviews an empirical study of public Facebook and Twitter communication associated with the pan-European protest against the Anti-Counterfeiting Trade Agreement. Ensuing results point to a rational, resource-oriented mode of communication figuring prominently on both platforms. Moreover, the time distribution of motivational and resource-driven talk confounds earlier claims about patterns of social media usage in collective action. Finally, despite their smaller number, motivational posts had a higher impact than resource-oriented talk on both platforms – an apparent sign of their particularly positive reception.